2016
DOI: 10.3126/mjsbh.v15i1.15042
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Versus Traditional Method in Basic Medical Science Education: A Comparative Study in an Indian Medical College

Abstract: Anatomy has always been a cornerstone of medical education disregard of nation or specialty. Dissection and didactic lectures were its only methods of teaching in the past. A multiple range of special study modules like integration, problem based approach and community based approach is now replacing where integration is not routinely practiced. Lectures of anatomy and physiology were integrated and students' understanding was assessed using pre-test and post-test in the form of 10 multiple-choice questions ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This is an alarming situation which shows that the perception of students towards clinical learning is largely ignored by the faculty as the teaching is too teacher centered. Studies have proven that student-centered teaching methodologies are better for medical education than traditional teachercentered methods in terms of orienting students for clinical learning [8], [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an alarming situation which shows that the perception of students towards clinical learning is largely ignored by the faculty as the teaching is too teacher centered. Studies have proven that student-centered teaching methodologies are better for medical education than traditional teachercentered methods in terms of orienting students for clinical learning [8], [15].…”
Section: Discussionmentioning
confidence: 99%
“…The low mean scores in item number 1, 2, 4, 5 and 8 are suggestive of this finding. Studies have concluded the necessity of integration of problem-based learning (PBL) and stimulation-based learning (SBE) techniques in preclinical years for the smooth transition of students when they enter in their clinical phase of learning [7], [8], [11]. Moreover, the incorporation of clinical skills sessions and case-based learning in the curriculum will improve students' preparedness for clinical years and reduce the burden caused by this transition [16], [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dilemma is the lag in effective feedback delivery in public sector institutes of developing countries due to extensive patient load and teacher-centered teaching [14]. These factors require a need to assess the knowledge and perception of students regarding the feedback they receive.…”
Section: Introductionmentioning
confidence: 99%